2018
DOI: 10.1002/tee.22623
|View full text |Cite
|
Sign up to set email alerts
|

A particular AC component protection scheme for bipolar HVDC transmission lines

Abstract: The line protection methods for high-voltage direct current (HVDC) transmission system in engineering applications are poor in sensitivity and reliability. In this paper, we introduce a new notion of energy, namely a particular AC energy, based on which a particular AC component protection scheme is proposed. The scheme is comprised of start-up criterion, fault identification criterion, and faulty pole identification criterion. The start-up criterion is based on the fact that particular AC component measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…If both relays identify the fault coming from forward, it is an internal fault. The fault direction can be determined by using (14). Thus, the fault discrimination criterion can be expressed as…”
Section: Fault Direction Discrimination and Fault Discrimination Crit...mentioning
confidence: 99%
See 2 more Smart Citations
“…If both relays identify the fault coming from forward, it is an internal fault. The fault direction can be determined by using (14). Thus, the fault discrimination criterion can be expressed as…”
Section: Fault Direction Discrimination and Fault Discrimination Crit...mentioning
confidence: 99%
“…Theoretically, the unit protection is able to protect the whole DC line. In [14, 15], pilot protections based on transient energy ratio of line boundary are proposed to detect high fault resistances. However, the voltage and current data at the measuring points (a, b, m and n) at the valve and line sides at both line ends are required to apply both schemes [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After analyzing the amplitudefrequency characteristics of the physical boundary consisted by smoothing reactor and DC filter on both sides of the HVDC transmission line, it is found that high-frequency signals are blocked by physical boundaries [2], which provides ideas to establish criteria by using high frequency energy. According to the attenuation characteristic of HVDC transmission line boundary elements to high frequency transient signals, references [3,4,5] respectively use wavelet energy, polar wave information entropy, and high frequency transient energy to quantitatively describe, analyze and estimate fault characteristics, so as to realize the identification of internal and external faults. These methods can effectively identify internal and external faults, but the threshold setting has no theoretical basis and requires numerous simulation verification.…”
Section: Introductionmentioning
confidence: 99%